1959
DOI: 10.1002/pol.1959.1203713104
|View full text |Cite
|
Sign up to set email alerts
|

Bulk viscosity of polymeric systems

Abstract: The theory of bulk viscosity as developed for the liquid state was applied to amorphous high polymeric systems. The isothermal volume contraction, the dependence of shear viscosity, and the fictive temperature of quenched high polymeric substances are all related to the bulk viscosity and explained by this theory. Simple representations are given for compressibility, bulk modulus, shear modulus, thermal expansion coefficient, and heat capacity, all of which are necessary to discuss the bulk viscosity. The theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
50
0

Year Published

1961
1961
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 239 publications
(53 citation statements)
references
References 25 publications
3
50
0
Order By: Relevance
“…Hirai et al 20 reported also that at T g , fg is constant and almost the same as that reported by Fox et al…”
supporting
confidence: 81%
“…Hirai et al 20 reported also that at T g , fg is constant and almost the same as that reported by Fox et al…”
supporting
confidence: 81%
“…If a fraction, x8, of the shear plane is covered by solid-like molecules and the remaining fraction, xa, by gas-like molecules, then the viscosity, -1, which is the ratio of shear stress, f, to rate of strain, the exponential gives the last form in equation (10). Since the sites are randomly distributed over the solid angle, the first term in the summation of equation (10) has the value 2iki cos 01 = 0 and the second term fX2X3X fX2X3X…”
mentioning
confidence: 99%
“…According to our vacancy liquid theory, a solid molecule can jump into all neighboring empty sites, so that (12), we have supposed the activation energy is a'E8V,/(V-V8) in accordance with Figure 2 and that the partition function for normal and activated states cancel out in the rate expression except for the reaction coordinate where the partition function for the normal state introduces the factor (1 -e-/T). Using Equations (11) and (12) to simplify (10) gives:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…First derivatives of the Gibbs free energy (volume (V) and entropy (S)) are continuous, whereas the second ones (heat capacity (c p ), thermal expansion coefficient (α p ) and compressibility (κ T )) change rapidly in the vicinity of Ehrenfest equations [15,16,17,18] …”
Section: Introductionmentioning
confidence: 99%